Food systems approach to addressing obesity in the Near East and North Africa region - Nanitashvili, Tamara (2020)
As part of the IFPRI Egypt Seminar in partnership with the FAO: “Food Policies and their Implications on Overweight and Obesity Trends in Selected Countries in MENA Region”